Charlotte's web - White E. B 1899-1985; E. B. White (New York : Scholastic, 1952)
Wilbur, the pig, is desolate when he discovers that he is destined to be the farmer's Christmas dinner until his spider friend, Charlotte, decides to help him.
M
680